(3GdJYQja HBOGH GdJCdjas - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3hHYO agPG JYQja dWja SejJg GdJYQja HBOGH GdJCdja s
(3BNQgG (B:s
(3ai eOM GdJYQja hGdWGdH GdXQja hGddg JYGdi CYde s
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B420s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(1027(3c(B) s
Keywords: (3GdeYGQa GdYGeIs